Chromosome-level genome assembly of the Durum wheat cultivar Langdon - Mengen Chen; Junlong Li; Yue Zhang; Yanmeng Ding; Wenjie Qin; Mengyuan Wu; Na Li; Cuicui Jin; Huili Wang; Shuo Chen; Dun Niu; Xiao Sun; et al. (Scientific Data)
Abstract Durum wheat (Triticum turgidum ssp. durum, 2n = 4x = 28, BBAA) is the second most cultivated lineage of wheat after hexaploid common wheat. Langdon is a prominent durum wheat cultivar, highly valued for its crucial role in the development of synthetic hexaploid wheat and its importance in agricultural research. Here, we present a high-quality chromosome-level genome assembly of Langdon using a combination of HiFi sequencing and high-throughput chromosome conformation capture (Hi-C) techniques. The total genome assembly size was 10.47 Gbp, with a benchmarking universal single-copy orthologs (BUSCO) score of 98.80%, consensus nucleotide quality value (QV) score of 50.31, long terminal repeat assembly index (LAI) value of 19.39, a scaffold N50 reached to 751.30 Mbp and a contig N50 value of 41.18 Mbp. Repetitive elements constituted 88.22% of the assembly, and 68,342 high confidence (HC) genes were annotated. The high-quality chromosome-level Langdon assembly can serve as a valuable reference for durum wheat, aiding gene research and comparative genomics, and leveraging synthetic hexaploid wheat’s genetic resources to advance global wheat improvement.